2013
DOI: 10.3126/saarctb.v9i2.7974
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Associated with Non-Adherence to Anti Tuberculosis Treatment in Sri Lanka

Abstract: Introduction: Sri Lanka had achieved a significant improvement in the tuberculosis control including a reduction of the default rate since introduction of the DOTS strategy to the National TB control Programme  in 1997. Patients’ adherence to anti TB treatment may be measured using either process oriented or outcome oriented definitions. Default rate is an outcome oriented definition that may be used as an indicator of poor patient adherence to anti TB treatment. One of the main obstacles in achieving the best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…2 Similarly, a study done in Sri Lanka showed that old age population were more prone to relapse, defaulter and treatment failure. 3 More than two-thirds (82%) of respondents were male which is consistent with study done in Pakistan by Afridi et al 4 This might be due to the reason that women had less access to diagnostic facilities than men. As well, males traveled more in areas of studies conducted.…”
Section: Resultssupporting
confidence: 82%
“…2 Similarly, a study done in Sri Lanka showed that old age population were more prone to relapse, defaulter and treatment failure. 3 More than two-thirds (82%) of respondents were male which is consistent with study done in Pakistan by Afridi et al 4 This might be due to the reason that women had less access to diagnostic facilities than men. As well, males traveled more in areas of studies conducted.…”
Section: Resultssupporting
confidence: 82%